2008
DOI: 10.1161/circulationaha.107.737023
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Region Ablation in Experimental Vagal Atrial Fibrillation

Abstract: Background-Pulmonary vein (PV) -encircling radiofrequency ablation frequently is effective in vagal atrial fibrillation (AF), and there is evidence that PVs may be particularly prone to cholinergically induced arrhythmia mechanisms. However, PV ablation procedures also can affect intracardiac autonomic ganglia. The present study examined the relative role of PVs versus peri-PV autonomic ganglia in an experimental vagal AF model. Methods and Results-Cholinergic AF was studied under carbachol infusion in coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(123 citation statements)
references
References 41 publications
5
115
0
3
Order By: Relevance
“…103,105,114,116,124,355,576,577,578,579,580,581,582 Because the GP are consistently located within areas of highly fractionated atrial potentials (FAPs), also referred to as CFAEs, 103,105,114,116,124,355,576,577,578,579,580,581,582,583,584 it is useful to begin with a fractionation map of the LA and PVs during AF. The LA FAPs are usually located in four areas: (1) LAA ridge FAP area (between LAA and left PVs); (2) superior left FAP area; (3) inferoposterior FAP area; and (4) anterior right FAP area (Figure 4).…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…103,105,114,116,124,355,576,577,578,579,580,581,582 Because the GP are consistently located within areas of highly fractionated atrial potentials (FAPs), also referred to as CFAEs, 103,105,114,116,124,355,576,577,578,579,580,581,582,583,584 it is useful to begin with a fractionation map of the LA and PVs during AF. The LA FAPs are usually located in four areas: (1) LAA ridge FAP area (between LAA and left PVs); (2) superior left FAP area; (3) inferoposterior FAP area; and (4) anterior right FAP area (Figure 4).…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…An interesting correlation of CFAEs with DFs and consequently vagal ganglia was also suggested by the electroanatomical mapping performed in our study. Therefore, based also on previous observations 72,73,138,143 , ablation of vagal ganglia during AF ablation could also be advantageous.…”
Section: Resultsmentioning
confidence: 88%
“…Our results are similar to previous work where AFCL was examined 71,117 . Moreover, recent studies showed high DF values after electric or ACh induced stimulation of cardiac autonomic ganglia 38,53,73,134,135 . However, to our knowledge this is the first study comparing the spectral properties of VS AF with ATR AF.…”
Section: Role Of Autonomic Ganglia Spiral Waves and Rotorsmentioning
confidence: 98%
“…Relation of GP ablation to outcome: Catheter ablation of GP has been shown to prevent vagal AF in canine models. 8,11,21) In recent clinical studies, vagal denervation was induced by targeted GP ablation 9,11,13,17) or inadvertently by standard circumferential or segmental PVI. 16,22) However, only limited data have been available on the long-term benefit of vagal denervation.…”
Section: Discussionmentioning
confidence: 99%